The Garden Suburb of Lindenlea, Ottawa: A Model Project for the First Federal Housing Policy, 1918–24 - Delaney, Jill (Urban History Review / Revue d'histoire urbaine, 1991)
The garden suburb of Lindenlea in Ottawa was designed by Thomas Adams and built by the Ottawa Housing commission to provide a model of low-income housing to municipalities across Canada in the post-World War One period. The planning of the suburb and the design of its houses reveal many of the ideological premises of the urban reform movement in Canada, and of the federal government's attitude toward publicly subsidized housing, in this early period of social welfare. Modern theories of rationalization, efficiency, and standardization, combined with late Victorian notions about physical, social and moral health, to produce housing designs that were technologically modern yet ideologically traditional.